INHOMOGENITY OF INNER STRUCTURE AND CHEMICAL COMPOSITION OF NATIVE COPPER OF VOLYN - Mysiak, І.; Скакун, Л.; Мисяк, I.; Косовський, Я.; Бондаренко, С.; Грінченко, О. (Київський національний університет імені Тараса Шевченка, 2012)
The native copper of Volyn is characterized by heterogeneous inner structure. Heterogeneity of the structure has been found on the results of structural etching and analysis of chemical composition of copper. Features of skeletal growth, oscillation growth zonality, splitting and block structure of crystals are established. Growth shapes show correlation with value of Ag/Fe ratio in copper. Growth and chemical inhomogenity can be explained according to the model of fluid mixing with different redox potential.

Самородна мідь Волині характеризується неоднорідною внутрішньою будовою. Неоднорідність будови виявлено за результатами досліджень форм структурного травлення і хімічного складу міді. Встановлено ознаки скелетного росту, осциляційної ростової зональності, розщеплення та блокової будови кристалів. Ростові форми корелюються із варіаціями співвідношення Ag/Fe в міді. Ростова та хімічна неоднорідність пояснюється в рамках моделі змішування розчинів із різним редокс-потенціалом.
НЕОДНОРІДНІСТЬ ВНУТРІШНЬОЇ БУДОВИ ТА ХІМІЧНОГО СКЛАДУ САМОРОДНОЇ МІДІ ВОЛИНІ